Anti-Inflammatory Benefits of Food Ingredients in Periodontal Diseases - Papathanasiou, Evangelos; Alreshaid, Reem; Araujo de Godoi, Mariely [UNESP] (MDPI, 2023)
Periodontitis is a multi-faceted inflammatory disease that impacts the gingiva and the structures that support our teeth, and may eventually increase tooth mobility and the risk of tooth loss. Inflammation is a viable therapeutic target of periodontitis for both biologic (dietary) and host modulatory agents/drugs. Conventional therapeutic approaches for periodontitis, including nonsurgical or surgical periodontal therapy as well as occasional adjunctive antimicrobial therapy, have been only marginally effective. Malnutrition, or at least poor dietary habits, can be highly prevalent among patients with periodontal diseases. As several food nutrients can aid in periodontal healing and regeneration, there is a critical need to evaluate natural dietary sources and supplement ingredients that can counterbalance the inflammatory processes and improve the periodontal status of our patients. Here, we reviewed the current state of knowledge (search period: 2010 to 2022; PubMed and Web of Science) on the anti-inflammatory actions of food ingredients and supplements in clinical studies of patients with periodontal diseases. A diet that includes fruits and vegetables, omega-3 polyunsaturated fatty acids, and supplements of vitamins and plant-derived compounds seems to counteract gingival inflammation and has a promising therapeutic impact in patients with periodontal diseases. Despite the positive indications that several nutrients can be used as an adjunct to periodontal therapy, additional studies with bigger sample sizes and longer follow-up periods are needed to elucidate their therapeutic benefits and the most effective doses and administration.
Keywords: gingivitis; immune response; inflammation; omega-3; periodontitis; polyphenols; supplements; vitamins